Fenomena Banjir Rob di Kota Semarang Sebagai Sumber Belajar - Gultom, Hana Torba; Juhadi, Juhadi; Aji, Ananto (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2018)
The research objective is to find out the phenomenon, impacts, efforts of the community and thegovernment in dealing with tidal flooding in the city of Semarang, and organizing the material ofthe tidal flood phenomenon in the city of Semarang as a learning resource. The sample area wastaken using a purposive technique, namely the Genuk District, North Semarang, and Tugu. Thesample of the community and the school to test the feasibility of the non-textbook using purposivesampling technique. Data analysis techniques using qualitative descriptive. The results of this studyindicate (1) the total area of Semarang City is 37,370 ha while the total area of threat, vulnerability,capacity, and risk of rob flood is 5,000, 72 ha (2) The impact of rob on the worst built environmentalaspects is the environment becomes 100% dirty, social aspects of population namely material lossesas much as 100%, built environmental aspects that damage road networks and damage to privatevehicles as much as 100% (3) Government efforts to control rob are divided into 3 regions, namelyWest Semarang, Central Semarang, and East Semarang, while , community efforts to deal with robvary according to household economic conditions. Tujuan penelitian untuk mengetahui fenomena, dampak, upaya masyarakat danpemerintah dalam menghadapi banjir rob di Kota Semarang. Sampel wilayah diambilmenggunakan teknik purposive yaitu wilayah Kecamatan Genuk, Semarang Utara, danTugu. Sampel masyarakat dan sekolah untuk menguji kelayakan buku nonteksmenggunakan teknik sampling purposive. Teknik analisis data menggunakan deskriptifkualitatif. Hasil penelitian ini menunjukkan (1) Total luas wilayah Kota Semarang37.370 ha sedangkan total luas ancaman, kerentanan, kapasitas, dan risiko banjir robyaitu 5.000, 72 ha (2) Dampak rob pada aspek lingkungan terbangun terparah yaitulingkungan menjadi kotor sebanyak 100%, aspek sosial kependudukan yaitu kerugianmaterial sebanyak 100%, aspek lingkungan terbangun yaitu merusak jaringan jalan danrusaknya kendaraan milik pribadi sebanyak 100% (3) Upaya pemerintah sebagai upayapengendalian rob dibagi menjadi 3 wilayah yaitu Wilayah Semarang Barat, SemarangTengah, dan Semarang Timur sedangkan, upaya masyarakat menghadapi rob beragamdisesuaikan keadaan perekonomian rumah tangga.